2014
DOI: 10.5901/mjss.2014.v5n15p249
|View full text |Cite
|
Sign up to set email alerts
|

“The Development of a Web-Based Homework System (WBH) Via TCExam”

Abstract: The aimed of the project is to develop and produce a web-based homework system (WBH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In the context of contribution to theories, this study highlights several important findings: first, the identification of students' attitudes and other roles that may influence academic performance and students' motivation to further studies at higher levels. This finding supports the findings of studies [20]. in which these studies have proven that the students' self-motivation and attitudes are able to improve their academic performance.…”
Section: Resultssupporting
confidence: 91%
“…In the context of contribution to theories, this study highlights several important findings: first, the identification of students' attitudes and other roles that may influence academic performance and students' motivation to further studies at higher levels. This finding supports the findings of studies [20]. in which these studies have proven that the students' self-motivation and attitudes are able to improve their academic performance.…”
Section: Resultssupporting
confidence: 91%
“…The study found that the most preferred "exam types" as assessment techniques based on faculty in higher education institutions are assignments, while the multiple-choice was the most common in vocational schools and high schools. Distribution, application, and retrieval of online assignments to students can be performed more quickly than traditional assignments, and also, the marking can be done without wasting time (Ismail, Mokhtar, Nasir, Rashid, & Ariffin, 2014). Today, fully automatic assignment evaluations can be performed through assignment evaluation modules in learning management systems.…”
Section: Discussionmentioning
confidence: 99%
“…The second group is the implementation of application program packages purchased in the market and implemented in companies, ranging from small software such as Microsoft retail products to integrated applications based on high technology [18]. The third group is the planning and development of specially made applications (customized software), both by internal organizations and in collaboration with external parties, such as consultants and software houses [19].…”
Section: System Development Methodsmentioning
confidence: 99%